2013
DOI: 10.3892/ijo.2013.2064
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic function of p34SEI-1 via NEDD4-1-mediated PTEN ubiquitination/degradation and activation of the PI3K/AKT pathway

Abstract: Abstract.A 34-KD protein encoded by the SEI-1 gene (p34 ), is a relatively recently discovered oncoprotein that has multiple important biological functions. Our data show that p34 SEI-1 enhances cancer cell survival and promotes tumorigenesis by downregulating the tumor suppressor PTEN, a negative regulator of the PI3K/AKT signaling pathway, and therefore activating the PI3K/AKT signaling pathway. In this process, p34 SEI-1 positively affects NEDD4-1 gene expression both at the transcriptional and protein lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 35 publications
1
60
0
Order By: Relevance
“…An independent study by Jung et al confirmed NEDD4-1 stabilization and PTEN degradation induced by p34SEI-1 overexpression [37]. Interestingly, p34SEI-1 overexpression also resulted in increased PTEN nuclear localization, suggesting again the possibly highly contextual nature of functional consequences of NEDD4-1's regulation of PTEN.…”
Section: Nedd4 (Nedd4-1)mentioning
confidence: 82%
See 2 more Smart Citations
“…An independent study by Jung et al confirmed NEDD4-1 stabilization and PTEN degradation induced by p34SEI-1 overexpression [37]. Interestingly, p34SEI-1 overexpression also resulted in increased PTEN nuclear localization, suggesting again the possibly highly contextual nature of functional consequences of NEDD4-1's regulation of PTEN.…”
Section: Nedd4 (Nedd4-1)mentioning
confidence: 82%
“…NEDD4-1 is frequently overexpressed in many types of human cancers including gastric carcinomas [35], colorectal [36], breast [37] and non-small cell lung carcinomas [38]. Suppression of NEDD4-1 expression in cells derived from these cancers can significantly reduce tumor cell growth both in vitro and in animal models.…”
Section: Nedd4 (Nedd4-1)mentioning
confidence: 99%
See 1 more Smart Citation
“…High PTEN expression may be due to the cancer cell proliferation and DNA double chain fractures (26,27). PTEN is one of the key regulation factors in the process of DNA repair and the expression is then increased in order for it to participate in the process of cancer development (26,27). In previous studies, PTEN was tested in PCa and hyperplastic prostate tissues, and it was observed to be mainly expressed in PCa tissues and in the cell nuclei of hyperplastic prostate tissues (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…High PTEN expression may be due to the cancer cell proliferation and DNA double chain fractures (26,27). PTEN is one of the key regulation factors in the process of DNA repair and the expression is then increased in order for it to participate in the process of cancer development (26,27).…”
Section: Discussionmentioning
confidence: 99%